Systematic Review ‐ Neuroprotection of ketosis in acute injury of the mammalian central nervous system: A meta‐analysis. Issue 2 (4th April 2021) - Gambardella, Ivancarmine; Ascione, Raimondo; D'Agostino, Dominic P.; Ari, Csilla; Worku, Berhane; Tranbaugh, Robert F.; Ivascu, Natalia; Villena‐Vargas, Jonathan; Girardi, Leonard N.
Abstract: To evaluate the neuroprotection exerted by ketosis against acute damage of the mammalian central nervous system (CNS). Search engines were interrogated to identify experimental studies comparing the mitigating effect of ketosis (intervention) versus non‐ketosis (control) on acute CNS damage. Primary endpoint was a reduction in mortality. Secondary endpoints were a reduction in neuronal damage and dysfunction, and an 'aggregated advantage' (composite of all primary and secondary endpoints). Hedges' g was the effect measure. Subgroup analyses evaluated the modulatory effect of age, insult type, and injury site. Meta‐regression evaluated timing, type, and magnitude of intervention as predictors of neuroprotection. The selected publications were 49 experimental murine studies (period 1979–2020). The intervention reduced mortality (g 2.45, SE 0.48, p < .01), neuronal damage (g 1.96, SE 0.23, p < .01) and dysfunction (g 0.99, SE 0.10, p < .01). Reduction of mortality was particularly pronounced in the adult subgroup (g 2.71, SE 0.57, p < .01). The aggregated advantage of ketosis was stronger in the pediatric (g 3.98, SE 0.71, p < .01), brain (g 1.96, SE 0.18, p < .01), and ischemic insult (g 2.20, SE 0.23, p < .01) subgroups. Only the magnitude of intervention was a predictor of neuroprotection (g 0.07, SE 0.03, p 0.01 per every mmol/L increase in ketone levels). Ketosis exerts a potent neuroprotection against acute damage to the mammalian CNS in terms of reduction of mortality, of neuronal damage and dysfunction. Hematic levels of ketones are directly proportional to the effect size of neuroprotection. Abstract : Acute injuries (AI) to the central nervous system (CNS) are a leading cause of mortality and disability. We performed an advanced meta‐analysis and regression of the body of evidence regarding the neuroprotection offered by ketosis after AI of the CNS in experimental mammalian models. Ketosis reduced mortality, neuronal damage and dysfunction. The level of hematic ketones was an independent predictor of neuroprotection. Besides targeted dietary regimens, the neuroprotection was significant also when ketosis was achieved via exogenous supplements. The latter consideration can prompt clinical trials to test the neuroprotection of exogenous ketones in humans with AI of the CNS.